An applet for optimal control problems - Rui Gonçalves (2007)
An Optimal Control Applet (OCA) is presented. This OCA is an Applet designed to study optimal control problems in an interactive manner. The graphical user interface (GUI) facilities the interaction with the user in several ways. First, the user is able to specify the key ingredients of an optimal control problem, namely controlled differential equations, control constraints and cost functions. Second, the user is allowed to specify specify the control inputs. These interactions are designed to support the cognitive process of learning the fundamentals of optimal control. The application is available for students over the net.